Efficient beam element model for analysis of composite beam with partial shear connectivity. (1st January 2023) - El-Sisi, Alaa; Alsharari, Fahad; Salim, Hani; Elawadi, Ali; Hassanin, Ahmed
Abstract: A two-node beam element formulation with eight degrees of freedom was developed and implemented into MATLAB to simulate the nonlinear behavior of the composite. The beam element includes the reinforced concrete slab, the concrete reinforcement, the steel beam, and the shear connectors. One dimension-softening model was used to simulate the concrete, the bilinear isotropic plastic model was used to simulate the steel, and a multi-linear spring was used to simulate the partial shear connectivity. Experimental results were used to validate the numerical model, which was able to closely predict the experimental response by a 2% difference. The model was able to simulate several material nonlinearities such as the plasticity of the steel beam and cracking and crushing of concrete slab. A parametric study was performed to investigate the effects of strength of shear connector, concrete slab thickness, steel beam depth, and the concrete compressive strength on the overall response of steel–concrete composite beams. It was found that the variation in shear connector strength significantly affects the response of the composite beams. In addition, the composite beam stiffness and strength increased with the increase of the steel beam depth, significantly.